Solid electrolyte material and battery using same

JP7634232B2Active Publication Date: 2025-02-21PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021574483
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-29
Filing Date
2020-11-25
Publication Date
2025-02-21
Estimated Expiration
2040-11-25

AI Technical Summary

Benefits of technology

【0006】 本開示は、低い融点および高いイオン伝導度を有する固体電解質材料を提供する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007634232000005
    Figure 0007634232000005
  • Figure 0007634232000006
    Figure 0007634232000006
  • Figure 0007634232000007
    Figure 0007634232000007
Patent Text Reader

Abstract

This solid electrolyte material is configured from Li, Y, X, and O, where X is one selected from the group consisting of F, Cl, Br, and I, and the molar ratio of O to Y is greater than 0.01 and less than 0.52.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a solid electrolyte material and a battery using the same.

Background Art

[0002] Patent Document 1 discloses an all-solid-state battery using a sulfide solid electrolyte. Patent Document 2 discloses a solid electrolyte material represented by Li 6-3z Y z [[ID=1第十六]]X6 (where 0 < z < 2 is satisfied and X is Cl or Br).

Prior Art Documents

Patent Documents

[0003]

Patent Document 1

Patent Document 2

Summary of the Invention

Problems to be Solved by the Invention

[0004] An object of the present disclosure is to provide a solid electrolyte material having a low melting point and high ionic conductivity.

Means for Solving the Problems

[0005] The solid electrolyte material of the present disclosure is composed of Li, Y, X, and O, where X is one selected from the group consisting of F, Cl, Br, and I, and the molar ratio of O to Y is greater than 0.01 and less than 0.52.

Effects of the Invention

[0006] The present disclosure provides a solid electrolyte material having a low melting point and high ionic conductivity.

Brief Description of the Drawings

[0007] [Figure 1] FIG. 1 shows a cross-sectional view of a battery 1000 according to a second embodiment. [Figure 2] FIG. 2 is a graph showing the X-ray diffraction patterns of the solid electrolyte materials according to Examples 1 to 3 and Comparative Example 1. [Figure 3] FIG. 3 shows a schematic diagram of a pressing die 300 used to evaluate the ionic conductivity of a solid electrolyte material. [Figure 4] FIG. 4 is a graph showing a Cole-Cole diagram of the impedance measurement results of the solid electrolyte material according to Example 1. [Figure 5] FIG. 5 is a graph showing the initial discharge characteristics of the battery according to Example 1. [Figure 6] FIG. 6 is a graph showing the results of thermal analysis of Examples 1 to 3 and Comparative Example 1. [Figure 7] FIG. 7 is a graph showing the X-ray diffraction patterns of the solid electrolyte materials according to Examples 4 to 6 and Comparative Examples 1 and 2. [Figure 8] FIG. 8 is a graph showing a Cole-Cole diagram of the impedance measurement results of the solid electrolyte material according to Example 4. [Figure 9] FIG. 9 is a graph showing the initial discharge characteristics of the battery according to Example 4. [Figure 10] FIG. 10 is a graph showing the results of thermal analysis of Examples 4 to 6 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE INVENTION

[0008] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.

[0009] (First embodiment) The solid electrolyte material according to the first embodiment is composed of Li, Y, X, and O. Here, X is one selected from the group consisting of F, Cl, Br, and I. The molar ratio of O to Y is greater than 0.01 and less than 0.52. The solid electrolyte material according to the first embodiment has a low melting point. Furthermore, the solid electrolyte material according to the first embodiment has high lithium ion conductivity. Here, a low melting point is, for example, 504°C or less. That is, the solid electrolyte material according to the first embodiment may have a melting point of, for example, 504°C or less. When the solid electrolyte material is a multiphase material, the melting point of the solid electrolyte material means the highest temperature among the melting points of the solid electrolyte material. Furthermore, high lithium ion conductivity is, for example, 1×10 -5 That is, the solid electrolyte material according to the first embodiment has a melting point of 504° C. or less and a viscosity of 1×10 -5 It may have an ionic conductivity of 5 S / cm or more.

[0010] The solid electrolyte material according to the first embodiment can be used to obtain an all-solid-state battery having excellent charge-discharge characteristics. The all-solid-state battery may be a primary battery or a secondary battery.

[0011] The solid electrolyte material according to the first embodiment desirably does not contain sulfur. A sulfur-free solid electrolyte material does not generate hydrogen sulfide even when exposed to the atmosphere, and is therefore highly safe. The sulfide solid electrolyte disclosed in Patent Document 1 may generate hydrogen sulfide when exposed to the atmosphere.

[0012] The solid electrolyte material according to the first embodiment may consist of Li, Y, X, and O only.

[0013] In order to increase the ionic conductivity of the solid electrolyte material, the solid electrolyte material according to the first embodiment may further contain at least one selected from the group consisting of Mg, Ca, Zn, Sr, Ba, Al, Sc, Ga, Bi, La, Zr, Hf, Ta, and Nb.

[0014] The transition metal contained in the solid electrolyte material according to this embodiment may be Y alone, excluding elements contained as inevitable impurities.

[0015] X may be Cl. Such a solid electrolyte material has a low melting point and high ionic conductivity.

[0016] Hereinafter, a first example and a second example of the solid electrolyte material according to the first embodiment will be described. The first example of the solid electrolyte material according to the first embodiment will be referred to as a "first solid electrolyte material," and the second example of the solid electrolyte material according to the first embodiment will be referred to as a "second solid electrolyte material."

[0017] (First solid electrolyte material) The X-ray diffraction pattern of the first solid electrolyte material can be measured using Cu-Kα radiation. The resulting X-ray diffraction pattern may have peaks at diffraction angles 2θ ranging from 15.2° to 16.4°, from 16.7° to 18.6°, from 30.8° to 31.9°, from 33.2° to 34.3°, from 40.3° to 41.4°, from 48.2° to 49.3°, and from 53.0° to 54.2°. Such a solid electrolyte material has a low melting point and high ionic conductivity.

[0018] To lower the melting point of the solid electrolyte material, the molar ratio of Li to Y may be 2.2 or more and 2.56 or less, and the molar ratio of X to Y may be 3.5 or more and 5.9 or less.

[0019] To further reduce the melting point of the solid electrolyte material, the molar ratio of Li to Y may be 2.49 or more and 2.56 or less, and the molar ratio of X to Y may be 3.91 or more and 5.29 or less.

[0020] The molar ratio of O to Y may be, for example, 1.0 or less.

[0021] The upper and lower limits of the molar ratio of O to Y can be defined by any combination selected from the following values: 0.01, 0.04, 0.23, and 0.50.

[0022] To lower the melting point of the solid electrolyte material, the molar ratio of O to Y may be greater than 0.01 and less than or equal to 0.50.

[0023] (Second solid electrolyte material) The molar ratio A of O to Y in the surface region of the second solid electrolyte material may be greater than the molar ratio B of O to Y in the entire second solid electrolyte material. Such a solid electrolyte material has a low melting point and high ionic conductivity. For example, the value of the molar ratio A may be more than twice the value of the molar ratio B.

[0024] Here, the surface region of the second solid electrolyte material means a region extending from the surface of the second solid electrolyte material to a depth of approximately 5 nm inward.

[0025] In order for the solid electrolyte material to have high ionic conductivity, the molar ratio A may be 2.50 or less.

[0026] The X-ray diffraction pattern of the second solid electrolyte material can be measured using Cu-Kα radiation. The resulting X-ray diffraction pattern may have peaks at diffraction angles 2θ of 15.2° to 16.3°, 16.7° to 18.5°, 30.8° to 31.9°, 33.1° to 34.2°, 40.3° to 41.4°, 48.2° to 49.3°, and 53.1° to 54.2°. Such solid electrolyte materials have a low melting point and high ionic conductivity.

[0027] In order for the solid electrolyte material to have a low melting point and high ionic conductivity, the molar ratio of O to Y in the entire second solid electrolyte material may be greater than 0.01 and equal to or less than 0.33.

[0028] The shape of the solid electrolyte material according to the first embodiment is not limited. Examples of the shape include a needle shape, a sphere shape, or an oval sphere shape. The solid electrolyte material according to the first embodiment may be in the form of particles. The solid electrolyte material according to the first embodiment may be formed into the shape of a pellet or a plate.

[0029] When the solid electrolyte material according to the first embodiment has a particulate (for example, spherical) shape, the solid electrolyte material according to the first embodiment may have a median diameter of 0.1 μm or more and 100 μm or less.

[0030] In order to enhance the ionic conductivity of the solid electrolyte material according to the first embodiment and to disperse the solid electrolyte material according to the first embodiment and the active material well, the median diameter may be 0.5 μm or more and 10 μm or less. The median diameter means the particle size when the cumulative volume in the volume-based particle size distribution is equal to 50%. The volume-based particle size distribution can be measured using a laser diffraction measurement device or an image analyzer.

[0031] In order to disperse the solid electrolyte material according to the first embodiment and the active material better, the solid electrolyte material according to the first embodiment may have a smaller median diameter than the active material.

[0032] <Method of manufacturing solid electrolyte material> The solid electrolyte material according to the first embodiment can be produced by the following method.

[0033] First, a plurality of halides are mixed together as raw material powders.

[0034] As an example, when preparing a solid electrolyte material consisting of Li, Y, Cl, and O, YCl3 raw material powder and LiCl raw material powder are mixed. The resulting mixed powder is fired in an inert gas atmosphere (e.g., an argon atmosphere with a dew point of -60°C or less) in which the oxygen and moisture concentrations are adjusted. The firing temperature may be, for example, in the range of 200°C to 650°C. The resulting reactant is left to stand in an atmosphere with a relatively high dew point (e.g., an argon atmosphere with a dew point of -30°C).

[0035] The reactants are then calcined at a temperature equal to or higher than the melting point (e.g., 550°C) in an inert gas atmosphere (e.g., an argon atmosphere having a dew point of -60°C or lower) in which the oxygen and moisture concentrations are adjusted. Calcination at a temperature equal to or higher than the melting point allows O to be present throughout the material. Alternatively, as another example, the reactants may be calcined at a temperature equal to or lower than the melting point (e.g., 400°C) in an inert gas atmosphere (e.g., an argon atmosphere having a dew point of -60°C or lower) in which the oxygen and moisture concentrations are adjusted. Calcination at a temperature lower than the melting point increases the proportion of O in the surface region of the solid electrolyte material.

[0036] The raw material powders may be mixed in a predetermined molar ratio to offset compositional changes that may occur during the synthesis process. The amount of oxygen in the solid electrolyte material is determined by selecting the raw material powders, the oxygen concentration in the atmosphere, the water concentration in the atmosphere, and the reaction time. In this way, the solid electrolyte material according to the first embodiment is obtained.

[0037] The raw material powders may be oxides and halides, for example, Y2O3, NH4Cl, and LiCl may be used as raw material powders.

[0038] It is believed that the oxygen constituting the solid electrolyte material according to the first embodiment is taken in from the atmosphere having the above-mentioned relatively high dew point.

[0039] (Second embodiment) The second embodiment will be described below. The matters described in the first embodiment may be omitted.

[0040] The battery according to the second embodiment includes a positive electrode, a negative electrode, and an electrolyte layer. The electrolyte layer is disposed between the positive electrode and the negative electrode. At least one selected from the group consisting of the positive electrode, the electrolyte layer, and the negative electrode contains the solid electrolyte material according to the first embodiment. The battery according to the second embodiment has excellent charge / discharge characteristics because it contains the solid electrolyte material according to the first embodiment.

[0041] A solid electrolyte material with a low melting point is softer than a solid electrolyte material with a higher melting point. This improves the adhesion between the solid electrolyte materials or between the solid electrolyte material and other materials (e.g., active materials). As a result, the battery resistance is reduced, improving the charge / discharge characteristics of the battery. Furthermore, even when the solid electrolyte material is sintered with other materials (e.g., active materials), the occurrence of side reactions can be suppressed.

[0042] FIG. 1 shows a cross-sectional view of a battery 1000 according to a second embodiment.

[0043] The battery 1000 includes a positive electrode 201 , an electrolyte layer 202 , and a negative electrode 203 .

[0044] The positive electrode 201 contains positive electrode active material particles 204 and solid electrolyte particles 100 .

[0045] The electrolyte layer 202 is disposed between the positive electrode 201 and the negative electrode 203 .

[0046] The electrolyte layer 202 contains an electrolyte material (eg, a solid electrolyte material).

[0047] The negative electrode 203 contains negative electrode active material particles 205 and solid electrolyte particles 100 .

[0048] The solid electrolyte particles 100 are particles made of the solid electrolyte material according to the first embodiment, or particles containing the solid electrolyte material according to the first embodiment as a main component. Here, particles containing the solid electrolyte material according to the first embodiment as a main component refer to particles in which the solid electrolyte material according to the first embodiment is the main component.

[0049] The positive electrode 201 contains a material capable of absorbing and releasing metal ions (for example, lithium ions). The material is, for example, a positive electrode active material (for example, positive electrode active material particles 204).

[0050] Examples of the positive electrode active material include a lithium-containing transition metal oxide, a transition metal fluoride, a polyanionic material, a fluorinated polyanionic material, a transition metal sulfide, a transition metal oxyfluoride, a transition metal oxysulfide, or a transition metal oxynitride. An example of a lithium-containing transition metal oxide is LiNi 1-d-f Co d Al f O2 (where 0 <d、0<f、かつ0<(d+f)<1)またはLiCoO2である。

[0051] In order to favorably disperse the positive electrode active material particles 204 and the solid electrolyte particles 100 in the positive electrode 201, the positive electrode active material particles 204 may have a median diameter of 0.1 μm or more. This favorable dispersion improves the charge / discharge characteristics of the battery 1000. In order to rapidly diffuse lithium within the positive electrode active material particles 204, the positive electrode active material particles 204 may have a median diameter of 100 μm or less. Due to the rapid diffusion of lithium, the battery 1000 can operate at a high output. As described above, the positive electrode active material particles 204 may have a median diameter of 0.1 μm or more and 100 μm or less.

[0052] In order to disperse the positive electrode active material particles 204 and the solid electrolyte particles 100 well in the positive electrode 201 , the positive electrode active material particles 204 may have a larger median diameter than the solid electrolyte particles 100 .

[0053] In order to increase the energy density and output of the battery 1000, in the positive electrode 201, the ratio of the volume of the positive electrode active material particles 204 to the sum of the volume of the positive electrode active material particles 204 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.

[0054] To increase the energy density and power output of the battery 1000, the positive electrode 201 may have a thickness of 10 μm or more and 500 μm or less.

[0055] The electrolyte layer 202 contains an electrolyte material. The electrolyte material may include the solid electrolyte material according to the first embodiment. The electrolyte layer 202 may be a solid electrolyte layer.

[0056] The electrolyte layer 202 may be made of only the solid electrolyte material according to the first embodiment, or may be made of only a solid electrolyte material different from the solid electrolyte material according to the first embodiment.

[0057] Examples of solid electrolyte materials different from the solid electrolyte material according to the first embodiment include Li2MgX'4, Li2FeX'4, Li(Al,Ga,In)X'4, Li3(Al,Ga,In)X'6, or LiI, where X' is at least one selected from the group consisting of F, Cl, Br, and I.

[0058] The electrolyte layer 202 may contain not only the solid electrolyte material according to the first embodiment, but also a solid electrolyte material different from the solid electrolyte material according to the first embodiment. The solid electrolyte material according to the first embodiment and the solid electrolyte material different from the solid electrolyte material according to the first embodiment may be uniformly dispersed. A layer made of the solid electrolyte material according to the first embodiment and a layer made of a solid electrolyte material different from the solid electrolyte material according to the first embodiment may be stacked along the stacking direction of the battery 1000.

[0059] In order to prevent short circuits between the positive electrode 201 and the negative electrode 203 and to increase the output of the battery 1000, the electrolyte layer 202 may have a thickness of 1 μm or more and 100 μm or less.

[0060] The negative electrode 203 contains a material capable of absorbing and releasing metal ions (for example, lithium ions). The material is, for example, a negative electrode active material (for example, negative electrode active material particles 205).

[0061] Examples of the negative electrode active material include a metal material, a carbon material, an oxide, a nitride, a tin compound, or a silicon compound. The metal material may be a simple metal or an alloy. An example of the metal material is lithium metal or a lithium alloy. Examples of the carbon material are natural graphite, coke, partially graphitized carbon, carbon fiber, spherical carbon, artificial graphite, or amorphous carbon. From the viewpoint of capacity density, suitable examples of the negative electrode active material are silicon (i.e., Si), tin (i.e., Sn), a silicon compound, or a tin compound.

[0062] In the negative electrode 203, in order to disperse the negative electrode active material particles 205 and the solid electrolyte particles 100 well, the negative electrode active material particles 205 may have a median diameter of 0.1 μm or more. This good dispersion improves the charge / discharge characteristics of the battery. In order to rapidly diffuse lithium within the negative electrode active material particles 205, the negative electrode active material particles 205 may have a median diameter of 100 μm or less. Due to the rapid diffusion of lithium, the battery can operate at a high output. As described above, the negative electrode active material particles 205 may have a median diameter of 0.1 μm or more and 100 μm or less.

[0063] In order to disperse the negative electrode active material particles 205 and the solid electrolyte particles 100 well in the negative electrode 203 , the negative electrode active material particles 205 may have a larger median diameter than the solid electrolyte particles 100 .

[0064] In order to increase the energy density and output of the battery 1000, in the negative electrode 203, the ratio of the volume of the negative electrode active material particles 205 to the sum of the volume of the negative electrode active material particles 205 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.

[0065] To increase the energy density and power output of the battery 1000, the negative electrode 203 may have a thickness of 10 μm or more and 500 μm or less.

[0066] In order to improve ionic conductivity, chemical stability, and electrochemical stability, at least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a solid electrolyte material different from the solid electrolyte material according to the first embodiment.

[0067] Examples of the solid electrolyte material include a halide solid electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte, or an organic polymer solid electrolyte.

[0068] Examples of halide solid electrolytes are Li2MgX'4, Li2FeX'4, Li(Al,Ga,In)X'4, Li3(Al,Ga,In)X'6, or LiI, where X' is at least one selected from the group consisting of F, Cl, Br, and I.

[0069] Examples of sulfide solid electrolytes are Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, or Li 10 GeP2S 12 is.

[0070] Examples of oxide solid electrolytes include: (i) NASICON-type solid electrolytes such as LiTi2(PO4)3 or its elemental substitutes; (ii) Perovskite-type solid electrolytes such as (LaLi)TiO3; (iii) Li 14 ZnGeO16 LISICON-type solid electrolytes such as Li4SiO4, LiGeO4, or elemental substitutions thereof; (iv) Li7La3Zr2O 12 or a garnet-type solid electrolyte such as an elemental substitution product thereof, or (v) Li3PO4 or its N-substituted derivatives is.

[0071] Examples of organic polymer solid electrolytes include polymer compounds and lithium salt compounds. The polymer compounds may have an ethylene oxide structure. Polymer compounds having an ethylene oxide structure can contain a large amount of lithium salt, thereby further increasing ionic conductivity.

[0072] Examples of lithium salts include LiPF, LiBF, LiSbF, LiAsF, LiSOCF, LiN(SOCF), LiN(SOCF) , LiN(SOCF)(SOCF), or LiC(SOCF). One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.

[0073] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a non-aqueous electrolyte, a gel electrolyte, or an ionic liquid in order to facilitate the exchange of lithium ions and improve the output characteristics of the battery 1000.

[0074] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.

[0075] Examples of non-aqueous solvents include cyclic carbonate ester solvents, chain carbonate ester solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents, and fluorine-containing solvents. Examples of cyclic carbonate ester solvents include ethylene carbonate, propylene carbonate, and butylene carbonate. Examples of chain carbonate ester solvents include dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate. Examples of cyclic ether solvents include tetrahydrofuran, 1,4-dioxane, and 1,3-dioxolane. Examples of chain ether solvents include 1,2-dimethoxyethane and 1,2-diethoxyethane. Examples of cyclic ester solvents include γ-butyrolactone. Examples of chain ester solvents include methyl acetate. Examples of fluorine-containing solvents include fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate, and fluorodimethylene carbonate.

[0076] One non-aqueous solvent selected from these may be used alone, or a mixture of two or more non-aqueous solvents selected from these may be used.

[0077] Examples of lithium salts include LiPF, LiBF, LiSbF, LiAsF, LiSOCF, LiN(SOCF), LiN(SOCF) , LiN(SOCF)(SOCF), or LiC(SOCF). One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.

[0078] The concentration of the lithium salt is, for example, in the range of 0.5 mol / liter to 2 mol / liter.

[0079] The gel electrolyte may be a polymer material impregnated with a non-aqueous electrolyte, such as polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.

[0080] Examples of cations contained in ionic liquids are: (i) aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium; (ii) aliphatic cyclic ammoniums such as pyrrolidiniums, morpholiniums, imidazoliniums, tetrahydropyrimidiniums, piperaziniums, or piperidiniums, or (iii) nitrogen-containing heterocyclic aromatic cations such as pyridiniums or imidazoliums is.

[0081] An example of an anion found in ionic liquids is PF6 - , BF4 - , SbF6 - , AsF6 - , SO3CF3 - , N(SO2CF3)2 - , N(SO2C2F5)2 - , N(SO2CF3)(SO2C4F9) - , or C(SO2CF3)3 - is.

[0082] The ionic liquid may contain a lithium salt.

[0083] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a binder for the purpose of improving adhesion between particles.

[0084] Examples of the binder include polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polyacrylic acid methyl ester, polyacrylic acid ethyl ester, polyacrylic acid hexyl ester, polymethacrylic acid, polymethacrylic acid methyl ester, polymethacrylic acid ethyl ester, polymethacrylic acid hexyl ester, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene-butadiene rubber, and carboxymethyl cellulose.

[0085] Copolymers can also be used as binders. Examples of such binders include copolymers of two or more materials selected from the group consisting of tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, and hexadiene. A mixture of two or more materials selected from these may also be used as a binder.

[0086] At least one selected from the positive electrode 201 and the negative electrode 203 may contain a conductive additive to enhance electronic conductivity.

[0087] Examples of the conductive additive include: (i) graphites such as natural or synthetic graphite; (ii) carbon blacks such as acetylene black or ketjen black; (iii) conductive fibers such as carbon or metal fibers; (iv) fluorocarbons, (v) metal powders such as aluminum; (vi) conductive whiskers such as zinc oxide or potassium titanate; (vii) a conductive metal oxide, such as titanium oxide, or (viii) Conductive polymer compounds such as polyaniline, polypyrrole, or polythiophene To reduce costs, the above-mentioned conductive additive (i) or (ii) may be used.

[0088] Examples of the shape of the battery according to the second embodiment include a coin type, a cylindrical type, a square type, a sheet type, a button type, a flat type, and a laminate type.

[0089] The battery according to the second embodiment may be manufactured, for example, by preparing a material for forming a positive electrode, a material for forming an electrolyte layer, and a material for forming a negative electrode, and by using a known method to fabricate a laminate in which the positive electrode, the electrolyte layer, and the negative electrode are arranged in this order. [Example]

[0090] Hereinafter, the present disclosure will be described in more detail with reference to examples.

[0091] Example 1 [Preparation of solid electrolyte materials] In an argon atmosphere having a dew point of -60°C or less and an oxygen concentration of 0.0001% by volume or less (hereinafter referred to as a "dry argon atmosphere"), raw material powders of YCl3 and LiCl were prepared in a molar ratio of 1:3. These raw material powders were ground and mixed in a mortar. The resulting mixture was fired in an alumina crucible at 550°C for 1 hour and then ground in the mortar. The resulting reactant was allowed to stand for approximately 10 minutes in an argon atmosphere having a dew point of -30°C and an oxygen concentration of 20.9% by volume. The reaction mixture was further fired in a dry argon atmosphere at 550°C for 1 hour and then ground in the mortar. In this manner, a solid electrolyte material according to Example 1 was obtained.

[0092] [Composition analysis of solid electrolyte materials] The Li and Y contents per unit weight of the solid electrolyte material according to Example 1 were measured by high-frequency inductively coupled plasma atomic emission spectroscopy using a high-frequency inductively coupled plasma optical emission spectrometer (iCAP7400, manufactured by Thermo Fisher Scientific). The Cl content of the solid electrolyte material according to Example 1 was measured by ion chromatography using an ion chromatograph (ICS-2000, manufactured by Dionex). Based on the Li, Y, and Cl contents obtained from these measurement results, the Li:Y:Cl molar ratio was calculated. As a result, the solid electrolyte material according to Example 1 had a Li:Y:Cl molar ratio of 2.56:1.00:5.29.

[0093] The mass ratio of O to the entire solid electrolyte material of Example 1 was measured by non-dispersive infrared absorption spectroscopy using an oxygen / nitrogen / hydrogen analyzer (EMGA-930, manufactured by Horiba, Ltd.). The mass ratio of O was found to be 0.22%. Based on this, the Y:O molar ratio was calculated. As a result, the solid electrolyte material of Example 1 had a Y:O molar ratio of 1.00:0.04.

[0094] In the composition analysis, elements with a molar ratio of 0.001% or less relative to Y were considered as impurities.

[0095] [Melt point measurement] A thermal analyzer (Q1000, manufactured by TA Instruments) was used to measure the melting point. Approximately 5 mg of the solid electrolyte material according to Example 1 was weighed out in a nitrogen atmosphere and heated from 300°C to 530°C at a heating rate of 10 K / min. An endothermic peak was observed at this time. Based on the obtained data, a two-dimensional graph was created with temperature on the horizontal axis and heat generation amount on the vertical axis. Two points on the graph where the solid electrolyte material neither generated nor absorbed heat were connected by a straight line, and this was used as the baseline. The melting point was then determined as the intersection of the tangent to the inflection point of the endothermic peak and the baseline. As a result, the melting point of the solid electrolyte material according to Example 1 was found to be 500.6°C. FIG. 6 is a graph showing the results of thermal analysis of the solid electrolyte material according to Example 1.

[0096] [X-ray diffraction] An X-ray diffraction apparatus (RIGAKU, MiniFlex600) was used to analyze the crystal structure of the solid electrolyte material. The X-ray diffraction pattern of the solid electrolyte material according to Example 1 was measured in a dry environment with a dew point of -45°C or less. Cu-Kα radiation (wavelengths 1.5405 Å and 1.5444 Å) was used as the X-ray source.

[0097] As a result of X-ray diffraction measurement, peaks were present at 15.83°, 18.03°, 31.37°, 33.72°, 40.85°, 48.74°, and 53.58°. Figure 2 is a graph showing the X-ray diffraction pattern of the solid electrolyte material according to Example 1.

[0098] [Evaluation of ionic conductivity] FIG. 3 shows a schematic diagram of a pressing die 300 used to evaluate the ionic conductivity of the solid electrolyte material.

[0099] The pressure molding die 300 had an upper punch 301, a frame 302, and a lower punch 303. The frame 302 was made of insulating polycarbonate. The upper punch 301 and the lower punch 303 were both made of electronically conductive stainless steel.

[0100] Using the pressure molding die 300 shown in FIG. 3, the ionic conductivity of the solid electrolyte material of Example 1 was measured by the following method.

[0101] In a dry argon atmosphere, powder 101 of the solid electrolyte material according to Example 1 was filled into a pressure molding die 300. Inside the pressure molding die 300, a pressure of 400 MPa was applied to the solid electrolyte material according to Example 1 using an upper punch 301 and a lower punch 303.

[0102] While the pressure was still applied, the upper punch 301 and the lower punch 303 were connected to a potentiostat (Princeton Applied Research, VersaSTAT4). The upper punch 301 was connected to a working electrode and a potential measurement terminal. The lower punch 303 was connected to a counter electrode and a reference electrode. The impedance of the solid electrolyte material according to Example 1 was measured at room temperature by an electrochemical impedance measurement method.

[0103] FIG. 4 is a graph showing a Cole-Cole diagram of the impedance measurement results of the solid electrolyte material according to Example 1.

[0104] In Fig. 4, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is smallest was considered to be the resistance value for ion conduction of the solid electrolyte material. The real value is indicated by the arrow R SE Using the resistance value, the ionic conductivity was calculated based on the following formula (1). σ=(R SE ×S / t) -1 ···(1)

[0105] where σ is the ionic conductivity, S is the contact area of ​​the solid electrolyte material with the punch upper portion 303 (equal to the cross-sectional area of ​​the hollow portion of the frame mold 301 in FIG. 3), and R SE is the resistance value of the solid electrolyte material in the impedance measurement, and t is the thickness of the solid electrolyte material to which pressure is applied (equivalent to the thickness of the layer formed from the powder 101 of the solid electrolyte material in FIG. 3).

[0106] The ionic conductivity of the solid electrolyte material according to Example 1 measured at 25°C was 2.4 × 10 -4 It was S / cm.

[0107] [Battery construction] In a dry argon atmosphere, the solid electrolyte material according to Example 1 and the active material LiCoO2 were prepared in a volume ratio of 70:30. These materials were mixed in an agate mortar. Thus, a mixture was obtained.

[0108] In an insulating cylinder having an inner diameter of 9.5 mm, the solid electrolyte material (100 mg) from Example 1, the above-mentioned mixture (10.0 mg), and aluminum powder (14.7 mg) were layered in this order. A pressure of 300 MPa was applied to this layered structure to form a first electrode and a solid electrolyte layer. The solid electrolyte layer had a thickness of 500 μm.

[0109] Next, a metal In foil was laminated on the solid electrolyte layer. The solid electrolyte layer was sandwiched between the metal In foil and the first electrode. The metal In foil had a thickness of 200 μm. Next, a pressure of 80 MPa was applied to the metal In foil to form the second electrode.

[0110] A current collector made of stainless steel was attached to the first electrode and the second electrode, and then a current collecting lead was attached to the current collector. Finally, an insulating ferrule was used to isolate the inside of the insulating tube from the outside atmosphere, and the inside of the tube was sealed. In this way, a battery according to Example 1 was obtained.

[0111] [Charge / discharge test] Fig. 5 is a graph showing the initial discharge characteristics of the battery according to Example 1. The results shown in Fig. 5 were measured by the following method.

[0112] The battery according to Example 1 was placed in a thermostatic chamber at 25°C. 2 The battery according to Example 1 was charged at a current density of 86 μA / cm 2 until a voltage of 3.7 V was reached, which corresponds to a 0.05 C rate. 2 The battery according to Example 1 was discharged at a current density of 0.1 V until a voltage of 1.9 V was reached.

[0113] As a result of the charge-discharge test, the battery according to Example 1 had an initial discharge capacity of 536 μAh.

[0114] Examples 2 and 3 A solid electrolyte material according to Example 2 was obtained in the same manner as in Example 1, except that the time during which the reactants were left standing in an atmosphere having a dew point of -30°C was changed from about 10 minutes to 30 minutes.

[0115] A solid electrolyte material according to Example 3 was obtained in the same manner as in Example 1, except that the time during which the reactants were allowed to stand in an atmosphere having a dew point of -30°C was changed from about 10 minutes to 9 hours.

[0116] The element ratios (molar ratios), melting points, oxygen contents, X-ray diffraction, and ionic conductivity of the solid electrolyte materials of Examples 2 and 3 were measured in the same manner as in Example 1. The measurement results are shown in Tables 1 and 2. FIG. 2 is a graph showing the X-ray diffraction patterns of the solid electrolyte materials of Examples 2 and 3. FIG. 6 is a graph showing the results of thermal analysis of the solid electrolyte materials of Examples 2 and 3.

[0117] Using the solid electrolyte materials of Examples 2 and 3, the batteries of Examples 2 and 3 were obtained in the same manner as in Example 1.

[0118] A charge-discharge test was carried out using the batteries according to Examples 2 and 3 in the same manner as in Example 1. The batteries according to Examples 2 and 3 were charged and discharged satisfactorily, similar to the battery according to Example 1.

[0119] (Comparative Example 1) In a dry argon atmosphere, raw material powders of YCl3 and LiCl were prepared in a molar ratio of 1:3. These raw material powders were ground and mixed in a mortar. The resulting mixture was fired in an alumina crucible at 550°C for 1 hour and then ground in the mortar. In this way, a solid electrolyte material according to Comparative Example 1 was obtained.

[0120] The element ratio (molar ratio), melting point, oxygen content, X-ray diffraction, and ionic conductivity of the solid electrolyte material of Comparative Example 1 were measured in the same manner as in Example 1. The measurement results are shown in Tables 1 and 2. FIG. 2 is a graph showing the X-ray diffraction pattern of the solid electrolyte material of Comparative Example 1. FIG. 6 is a graph showing the results of thermal analysis of the solid electrolyte material of Comparative Example 1.

[0121] [Table 1]

[0122] [Table 2]

[0123] (Consideration) As is clear from Table 1, the solid electrolyte materials according to Examples 1 to 3 have a lower melting point than the solid electrolyte material according to Comparative Example 1. Furthermore, the solid electrolyte materials according to Examples 1 to 3 have a melting point of 1×10 -5 It has high ionic conductivity of over S / cm.

[0124] The batteries according to Examples 1 to 3 were charged and discharged at 25°C.

[0125] The solid electrolyte materials according to Examples 1 to 3 do not contain sulfur and therefore do not generate hydrogen sulfide.

[0126] Example 4 [Preparation of solid electrolyte materials] In a dry argon atmosphere, raw material powders of YCl3 and LiCl were prepared in a molar ratio of 1:3. These raw material powders were ground and mixed in a mortar. The resulting mixture was fired in an alumina crucible at 550°C for 1 hour and then ground in the mortar. The resulting reactant was left to stand for approximately 10 minutes in an argon atmosphere with a dew point of -30°C and an oxygen concentration of 20.9% by volume. The resulting mixture was further fired in a dry argon atmosphere at 400°C for 1 hour and then ground in the mortar. In this way, a solid electrolyte material according to Example 4 was obtained.

[0127] [Composition analysis of solid electrolyte materials] The contents of Li, Y, and Cl in the entire solid electrolyte material of Example 4 were measured, and the Li:Y:Cl molar ratio was calculated in the same manner as in Example 1. As a result, the solid electrolyte material of Example 4 had a Li:Y:Cl molar ratio of 2.56:1.00:5.16.

[0128] The mass ratio of O to the entire solid electrolyte material of Example 4 was measured in the same manner as in Example 1. As a result, the mass ratio of O was 0.29%. Based on this, the Y:O molar ratio was calculated. As a result, the solid electrolyte material of Example 4 had a Y:O molar ratio of 1.00:0.06.

[0129] The molar ratio of O to Y in the surface region of the solid electrolyte material according to Example 4 was measured by X-ray photoelectron spectroscopy using a scanning X-ray photoelectron spectrometer (PHI Quantera SXM, manufactured by ULVAC-PHI). Al-Kα radiation was used as the X-ray source. As a result, the solid electrolyte material according to Example 4 had a Y:O molar ratio of 1.00:0.15 in the surface region. The surface region in this disclosure refers to the region measured in this manner. The thickness of the surface region of the solid electrolyte material according to Example 4 was approximately 5 nm from the surface toward the interior of the solid electrolyte material.

[0130] In the composition analysis, elements with a molar ratio of 0.001% or less relative to Y were considered as impurities.

[0131] [Melt point measurement] The melting point of the solid electrolyte material according to Example 4 was measured in the same manner as in Example 1. As a result, the melting point of the solid electrolyte material according to Example 4 was 498.8° C. Fig. 10 is a graph showing the results of thermal analysis of the solid electrolyte material according to Example 4.

[0132] [X-ray diffraction] In the same manner as in Example 1, the X-ray diffraction pattern of the solid electrolyte material of Example 4 was measured.

[0133] As a result of X-ray diffraction measurement, peaks were present at 15.79°, 17.99°, 31.33°, 33.67°, 40.84°, 48.74°, and 53.56°. Figure 7 is a graph showing the X-ray diffraction pattern of the solid electrolyte material according to Example 4.

[0134] [Charge / discharge test] Using the solid electrolyte material of Example 4, a battery of Example 4 was obtained in the same manner as in Example 1.

[0135] Fig. 9 is a graph showing the initial discharge characteristics of the battery according to Example 4. The results shown in Fig. 9 were measured by the following method.

[0136] The battery according to Example 4 was placed in a thermostatic chamber at 25°C. 2 The battery according to Example 7 was charged at a current density of 83 μA / cm 2 until a voltage of 3.7 V was reached, which corresponds to a 0.05 C rate. 2 The battery according to Example 4 was discharged at a current density of 1.9 V until a voltage of 1.9 V was reached.

[0137] As a result of the charge-discharge test, the battery according to Example 4 had an initial discharge capacity of 642 μAh.

[0138] Examples 5 and 6 A solid electrolyte material according to Example 5 was obtained in the same manner as in Example 4, except that the time during which the reactants were left standing in an atmosphere having a dew point of -30°C was changed from about 10 minutes to 30 minutes.

[0139] A solid electrolyte material according to Example 6 was obtained in the same manner as in Example 4, except that the time during which the reactants were allowed to stand in an atmosphere having a dew point of -30°C was changed from about 10 minutes to 2 hours.

[0140] The element ratios (molar ratios), melting points, oxygen contents, X-ray diffraction, and ionic conductivity of the solid electrolyte materials of Examples 5 and 6 were measured in the same manner as in Example 4. The measurement results are shown in Tables 3 and 4. FIG. 7 is a graph showing the X-ray diffraction patterns of the solid electrolyte materials of Examples 5 and 6. FIG. 10 is a graph showing the results of thermal analysis of the solid electrolyte materials of Examples 5 and 6.

[0141] Using the solid electrolyte materials of Examples 5 and 6, the batteries of Examples 5 and 6 were obtained in the same manner as in Example 1.

[0142] A charge-discharge test was carried out using the batteries according to Examples 5 and 6 in the same manner as in Example 4. The batteries according to Examples 5 and 6 were charged and discharged as well as the battery according to Example 4.

[0143] (Comparative Example 2) A solid electrolyte material according to Comparative Example 2 was obtained in the same manner as in Example 7, except that the time during which the reactants were left standing in an atmosphere having a dew point of -30°C was changed from about 10 minutes to 9 hours.

[0144] The element ratios (molar ratios), melting points, oxygen contents, X-ray diffraction, and ionic conductivity of the solid electrolyte materials of Comparative Examples 1 and 2 were measured in the same manner as in Example 7. The measurement results are shown in Tables 3 and 4. FIG. 7 is a graph showing the X-ray diffraction patterns of the solid electrolyte materials of Comparative Examples 1 and 2. FIG. 10 is a graph showing the results of thermal analysis of the solid electrolyte materials of Comparative Examples 1 and 2.

[0145] Using the solid electrolyte material of Comparative Example 2, a battery of Comparative Example 2 was obtained in the same manner as in Example 4.

[0146] A charge-discharge test was carried out using the battery of Comparative Example 2 in the same manner as in Example 4, but the initial discharge capacity was 1 mAh or less. The battery of Comparative Example 2 was neither charged nor discharged.

[0147] [Table 3]

[0148] [Table 4]

[0149] (Consideration) As is clear from Table 3, the solid electrolyte materials according to Examples 4 to 6 have a lower melting point than the solid electrolyte material according to Comparative Example 1. Furthermore, the solid electrolyte materials according to Examples 4 to 6 have a melting point of 1×10 -5 On the other hand, the solid electrolyte material according to Comparative Example 2 has a high ionic conductivity of 1×10 -5 It has an ionic conductivity of less than S / cm.

[0150] As is clear from Table 3, when the molar ratio of O to Y in the entire solid electrolyte material is greater than 0.01 and not more than 0.33, the solid electrolyte material has a low melting point and high ionic conductivity.

[0151] The batteries according to Examples 4 to 6 were charged and discharged at 25°C.

[0152] The solid electrolyte materials according to Examples 4 to 6 do not contain sulfur and therefore do not generate hydrogen sulfide.

[0153] As described above, the solid electrolyte material according to the present disclosure has a low melting point and high lithium ion conductivity, and is suitable for providing a battery that can be charged and discharged well. [Industrial Applicability]

[0154] The solid electrolyte material of the present disclosure is used, for example, in an all-solid-state lithium-ion secondary battery. [Explanation of symbols]

[0155] 100 solid electrolyte particles 101 Solid electrolyte material powder 201 Positive electrode 202 Electrolyte layer 203 Negative electrode 204 Positive electrode active material particles 205 Negative electrode active material particles 300 pressure forming die 301 Punch top 302 Frame type 303 Punch bottom 1000 batteries

Claims

1. Consisting of Li, Y, X, and O; where X is one selected from the group consisting of F, Cl, Br, and I; the molar ratio of O to Y is greater than 0.01 and less than or equal to 0.50; the molar ratio of Li to Y is 2.2 or more and 2.56 or less; The molar ratio of X to Y is 3.5 or more and 5.9 or less; Solid electrolyte material.

2. X is Cl; The solid electrolyte material according to claim 1 .

3. Further comprising at least one selected from the group consisting of Mg, Ca, Zn, Sr, Ba, Al, Sc, Ga, Bi, La, Zr, Hf, Ta, and Nb; The solid electrolyte material according to claim 1 or 2.

4. In an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα, peaks are present in the ranges of diffraction angle 2θ of 15.2° to 16.4°, 16.7° to 18.6°, 30.8° to 31.9°, 33.2° to 34.3°, 40.3° to 41.4°, 48.2° to 49.3°, and 53.0° to 54.2°. The solid electrolyte material according to claim 1 .

5. the molar ratio of O to Y in a surface region of the solid electrolyte material is greater than the molar ratio of O to Y in the entire solid electrolyte material; The solid electrolyte material according to claim 1 .

6. In an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα, peaks are present in the ranges of diffraction angle 2θ of 15.2° to 16.3°, 16.7° to 18.5°, 30.8° to 31.9°, 33.1° to 34.2°, 40.3° to 41.4°, 48.2° to 49.3°, and 53.1° to 54.2°. The solid electrolyte material according to any one of claims 1 to 3 and 5.

7. The molar ratio of O to Y in the entire solid electrolyte material is greater than 0.01 and less than or equal to 0.33; The solid electrolyte material according to any one of claims 1 to 3, 5, and 6.

8. positive electrode, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode; Equipped with At least one selected from the group consisting of the positive electrode, the negative electrode, and the electrolyte layer contains the solid electrolyte material according to any one of claims 1 to 7. battery.

Citation Information

Patent Citations

  • Garnet-type lithium ion-conducting oxide

    JP2010202499A

  • Method of manufacturing sulfide solid electrolyte material, sulfide solid electrolyte material, and lithium battery

    JP2011129312A

  • Solid electrolyte material, and cell

    WO2018025582A1

  • Electrode material and battery

    WO2019146308A1

  • Solid electrolyte, solid electrolyte layer, and solid electrolyte cell

    WO2021024785A1